2022
DOI: 10.1177/21676968221119945
|View full text |Cite
|
Sign up to set email alerts
|

College, Interrupted: Profiles in First-Year College Students Responses to the COVID-19 Pandemic Across One Year

Abstract: First-year college students in the 2019-2020 academic year are at risk of having their mental health, identity work, and college careers derailed as a result of the COVID-19 pandemic. To assess emerging and evolving impacts of the pandemic on mental health/well-being, identity development, and academic resilience, we collected data from a racially, ethnically, geographically, and economically diverse group of 629 students at four universities across the US within weeks of lockdown, and then followed up on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 65 publications
0
12
1
Order By: Relevance
“…Unfortunately, this is not what unfolded, and we adapted to collect data over the following year. We report full analyses on the self-report questionnaires elsewhere (Pasupathi et al, 2022). Briefly, we found that COVID-19 stressors were negatively associated with psychosocial adjustment and identity development and positively associated with internalizing and externalizing problems across time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this is not what unfolded, and we adapted to collect data over the following year. We report full analyses on the self-report questionnaires elsewhere (Pasupathi et al, 2022). Briefly, we found that COVID-19 stressors were negatively associated with psychosocial adjustment and identity development and positively associated with internalizing and externalizing problems across time.…”
mentioning
confidence: 99%
“…In the current work, we focused on the narratives collected at the first time point in relation to both concurrent and longitudinal (1 year later) well-being and identity work. This focus on two time points, rather than trajectories of change over multiple time points, was based on our attempts to minimize deviations from our preregistration and on limited evidence of linear change for many student outcomes (see Pasupathi et al, 2022).…”
mentioning
confidence: 99%
“…For EA this was evident in difficulties with identity issues, the focal development task of the period. Similarly, Pasupathi et al (2022) found increases in maladaptive exploration as well as decreases in mental health and academic resilience in a follow-up of first-year university students over the first year of the pandemic, and this was greatest among students with elevated baseline psychological symptoms. It would be useful for further research to address specific identity concerns that are most relevant to students in such precarious times and how these may vary across individuals and contexts (Galliher et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…Another consideration is that T2 data were collected during active shelter-in-place orders wherein all students were engaged in online instruction only due to COVID-19. Research has illustrated that shifts to online learning spaces and social distancing measures have been linked with aspects such as loneliness and declines in college belongingness (Birmingham et al, 2021 ; Pasupathi et al, 2022 ). The frequency and variety of peer interactions were reduced in the context of online learning, perhaps making it less likely that individuals would receive the same forms of peer support as they would within in-person learning contexts.…”
Section: Discussionmentioning
confidence: 99%
“…A different pattern of stability coefficients for peer support and academic competence may have been observed for students in younger developmental stages, such as first-year students that may have fewer social connections and less academic experience within the college context. Indeed, longitudinal examinations of first-year college students during the onset of the pandemic have showed increased perceptions of COVID-19 related loneliness (Mehus et al, 2021 ) and declines in areas of academic functioning, such as college self-efficacy and belongingness (Pasupathi et al, 2022 ). The results also showed stability in anxiety symptoms, indicating that college students reporting higher anxiety symptoms before the pandemic continued to report higher levels during the onset of COVID-19.…”
Section: Discussionmentioning
confidence: 99%